2022
DOI: 10.7759/cureus.26263
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experiences With a Remote Monitoring Pathway for COVID-19

Abstract: Introduction: Due to the coronavirus disease 2019 (COVID-19) pandemic, a remote monitoring pathway was developed at Michael Garron Hospital to allow individuals with confirmed or presumed COVID-19 infection to successfully manage their illness at home. This study aims to understand patients' experiences on this remote monitoring pathway and to investigate the effectiveness of the pathway in preventing unnecessary emergency department (ED) visits and detecting severe infection.Methods: A total of 35 semi-struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Reductions in health care costs, hospital readmission, and increased access to care with better clinical outcomes and patient satisfaction are some of the potential benefits associated with this innovative strategy of offering health care outside of traditional clinical settings [16,19,21,[29][30][31]. Furthermore, patients expressed feeling more informed about their condition and more connected with their providers when continuous monitoring was provided [32,33]. Similarly, health care providers have experienced a high level of acceptance in the inclusion of RPM as part of their daily practice [19,34].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Reductions in health care costs, hospital readmission, and increased access to care with better clinical outcomes and patient satisfaction are some of the potential benefits associated with this innovative strategy of offering health care outside of traditional clinical settings [16,19,21,[29][30][31]. Furthermore, patients expressed feeling more informed about their condition and more connected with their providers when continuous monitoring was provided [32,33]. Similarly, health care providers have experienced a high level of acceptance in the inclusion of RPM as part of their daily practice [19,34].…”
Section: Principal Findingsmentioning
confidence: 99%
“…This facilitated a space to connect with patients when in-person therapy was halted during the initial lockdown. Remote monitoring reduces patients' travel costs and risk for infection (Cheng et al, 2022;Annie et al, 2020). Therapists indicated that remote monitoring in the early stages of the pandemic provided opportunities for patients to acquire information about COVID-19, rehabilitation, and their general medical management.…”
Section: Remote Monitoring Telepracticementioning
confidence: 99%
“…[4][5][6] Reassuringly, VWs have maintained relatively robust safety profiles and patient satisfaction, whilst avoiding common complications associated with hospital admissions. [7][8][9] Despite these benefits, equitable access remains a challenge for patient care, with striking disparity in terms of technological access and connectivity, digital literacy, language barriers and socioeconomic status. 10,11 In addition, risk categorisation and escalation pathways remain divergent across health services, in part due to the rapidly changing nature of the pandemic and the associated evolution of variants, vaccinations and treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems have been further supported by the implementation of remote monitoring mechanisms that allow earlier identification of well‐described phenomena such as ‘silent hypoxaemia’ 4–6 . Reassuringly, VWs have maintained relatively robust safety profiles and patient satisfaction, whilst avoiding common complications associated with hospital admissions 7–9 …”
Section: Introductionmentioning
confidence: 99%